Molecular docking study of binding modes of amphetamine, cathine, and cathinone to monoamine oxidase B - Jerah A Ahmed (Wolters Kluwer Medknow Publications, 2019)
Background Molecular docking is commonly used in the study of small-molecule-protein interaction. Amphetamine (AMPH), cathine (CATHI), and cathinone (CATHO) bind in silico with monoamine oxidase B (MAO B) with relatively low affinity. Objective The purpose of the study was to determine the binding modes of AMPH, CATHI, and CATHO with the enzyme MAO B. Molecular docking software, AutoDock 4.2, was used to study the interaction of these ligands with MAO B. Materials and methods Molecular docking was performed using the molecular docking software AutoDock, version 4.2. graphic user interface, AutoDock Tools, was used to prepare protein and ligands for docking. Results The estimated ΔG of binding (free energy of binding) was −6.25 kcal/mol for AMPH, −6.05 kcal/mol for CATHI, and −6.24 kcal/mol for CATHO. Respective Ki (inhibitor constant) values were 2.61×10−5 M, 3.69×10−5 M, and 2.69×10−5 M. All three ligands show similar interactions within active site which include hydrophobic and hydrogen-bonding interactions. When compared with binding affinity of known inhibitors of MAO, safinamide, the binding affinity of these inhibitors is substantially less. But, they bind in the same active site and share some common interactions with active site residues. Similarity in binding modes of AMPH, CATHI, and CATHO is due to their similar structures. Conclusion It can be speculated that nervous stimulant activity of AMPH, CATHI, and CATHO could be due to inhibition of MAO. This enzyme catalyzes the oxidative deamination of monoamine neurotransmitters such as serotonin and dopamine and reduces the level of these neurotransmitters. Inhibition of this enzyme might result in more sustained levels of these neurotransmitters. Our docking study shows that AMPH, CATHI, and CATHO inhibit MAO B with free energy ranging from −6.05 to −6.25 kcal/mol and Ki ranging from 2.61×10−5 to 3.69×10−5 M.